Socialization and Training on Preparing Financial Reports for Officials in Amyu Village, East Arso District, Keerom Regency, Papua Province Who Experience Difficulty in Preparing End of Year Financial Reports - Heluka, Elius; Baasalem, Fachri; Tanudy, Ayub (PT Inovasi Pratama Internasional, 2024)
This service activity is carried out by providing outreach And training preparation report finance for apparatus village . This socialization and training was carried out to provide direction on how to input village financial data so that camp officials can understand and apply how to prepare financial reports properly . The expected objectives of this activity are ; a) to train officials in preparing financial reports, b) to increase understanding of the preparation of financial reports and c) properly apply the results of training in preparing year-end financial reports. The method used is​​ lectures, tutorials and discussions on traditional para-para. Results of socialization and training in preparing financial reports for Amyu village apparatus is to provide understanding and ability to village officials and village consultative bodies to be able to prepare end-of-year financial reports properly so that funds enter the village on time and are managed transparently, openly and honestly in accordance with established regulations. During the implementation of the activity, all participants were enthusiastic, including the village head (karateker), who attended the event until it was finished and felt the benefits of socialization and training in preparing year-end financial reports, which is only the job of the village head and village assistant, but also many people understand directly the methods and mechanisms. preparation report finance.